Comparative evaluation of H1 receptor blocking activity and safety of newer H1antagonist mizolastine with loratadine and placebo: a randomized double blind three way crossover study - K., Swarnalatha; Sonia, S. Sharon; Reddy, C. Prabahkar; Rao, Ramesh Kumar; R Naidu, M. U. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Histamine is a naturally occurring body constituent synthesized from L-histidine by histidine decarboxylase enzyme that is expressed throughout the body including central nervous system neurons, gastric mucosa, mast cells and basophils. The objective of this study was to compare the pharmacological activity and safety of 10 mg mizolastine, 10 mg loratadine and placebo in healthy human volunteers. Methods: After randomly allocating the 3 drugs, a battery of psychometric tests was done. Histamine prick test for wheal and flare reaction, VAS for sedation and itch followed by salivary flow test were done. Vitals were recorded. The subjects were randomized to receive either of the treatment in a cross-over manner with washout period of 7 days. The wheal and flare areas were recorded before and after 1,2,4,8, and 24 hours. Results: Mean inhibition on histamine induced wheal and flare response with mizolastine was highly significant as compared to placebo from 1 hour onwards (p<0.001) with maximum inhibition of 98.1±1.8% at 4 hours and of 85.1±24.8percent at 8 hours, for wheal and flare, respectively. The mean inhibition on histamine induced response with loratadine was significant from 2 hours (p<0.05) for wheal area and 1 hour onwards up to 24 hours (P<0.01) for flare area with the maximum inhibition of 56.2±31.6 percent and 60.1±14.2percent at 8hours, respectively. Mean inhibition on histamine induced itch with mizolastine was also significant from 4 hours onwards and persisted up to 24 hours (p<0.05) with maximum inhibition of 58.6±54.2% at 8 hours for the itch response, unlike loratidine. There was no significant change in mean effect on sedation assessed on a VAS of 0-100 mm. There was no significant change in psychomotor functions, salivary flow or vital parameters. All were well tolerated. Conclusions: Mizolastine has good antihistaminic activity than loratadine. Neither drug causes any psychomotor impairment or has anti-cholinergic action.